Audit Infrastruktur IT Dalam Memenuhi Kebutuhan Bisnis (Studi Kasus : Perusahaan Yang Begerak Pada Bidang Jasa) - Deval Gusrion (Universitas Putra Indonesia YPTK Padang, 2021)
The audit of the Information Technology infrastructure in this journal uses the ISO 27001 standard which is carried out at a company engaged in the service sector in West Sumatra Province. As a company that is quite developed and already has an adequate IT infrastructure in running its business, it is felt necessary to carry out an IT audit to ensure whether the IT devices they have already have adequate internal controls and at the same time as preventive measures for business risks such as: operational, reputation , legal, compliance and strategic. Given that IT is an important asset in operations that can increase the added value and competitiveness of a company while its implementation contains various risks, companies need to implement IT Governance.